2018
DOI: 10.1108/ajems-06-2017-0139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the long-term trade-off between efficiency and value creation in horizontal M&As

Abstract: Purpose The purpose of this paper is to investigate the voluntary horizontal M&A impact on operating performance in Nigeria between 1995 and 2012 under different complementary approaches. Design/methodology/approach Residual income valuation (RIV), economic value-added (EVA), data envelopment analysis (DEA) and stochastic frontier analysis (SFA). Findings Results showed a statistically significant improvement in the technical efficiency of both bidder and target companies, the reduced efficiency levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…It seems to support Modogliani and Miller (1958) postulation that capital structure of entities is irrelevance. However, the result did not support Lukman (2020),Abanum & Ebiaghan (2022) Abdelrahman and Elgiziry (2019), Akpan et al, (2018), andDaniya et al, (2016) that found positive and significant change in capital structure due to merger and acquisition. The result probably suggests that the consolidation has pulled funds from merged banks, and less reliability on debt (Tarila & Ogege, 2019;Taiwo & Musa, 2014).…”
Section: 52mentioning
confidence: 74%
“…It seems to support Modogliani and Miller (1958) postulation that capital structure of entities is irrelevance. However, the result did not support Lukman (2020),Abanum & Ebiaghan (2022) Abdelrahman and Elgiziry (2019), Akpan et al, (2018), andDaniya et al, (2016) that found positive and significant change in capital structure due to merger and acquisition. The result probably suggests that the consolidation has pulled funds from merged banks, and less reliability on debt (Tarila & Ogege, 2019;Taiwo & Musa, 2014).…”
Section: 52mentioning
confidence: 74%
“…Banking operations should also be related to efficiency (Chitnis & Vaidya, 2018). There is a kind of synergy between the non-performing financing (NPF) ratio and the operating expense and operating income (BOPO) ratio , which is further included regarding the efficiency indicators of Islamic banking which are proxied by the two ratio (Akpan et al, 2018). Based on Figure 3 about the average of NPF, BOPO, as well as the financing to deposit ratio or FDR (Hess & Francis, 2004), it can be observed that the bad debts ratio for the last five years (2015-2019) from Islamic banks is classified as good because it is still around less than 5 per cent.…”
Section: Yudha Indrawan Syarifudinmentioning
confidence: 99%
“…While operating income is the main income of a bank, namely income obtained from the placement of funds in the form of credit or financing and other operating income (Hess & Francis, 2004). The relationship that is formed between BOPO and the level of efficiency is that the smaller the BOPO, the more efficient the bank is in carrying out its business activities (Akpan et al, 2018), and vice versa. For a bank that has a healthy condition, the BOPO ratio is less than one; on the other hand, a less healthy bank, the BOPO ratio is more than one.…”
Section: Operating Expense Operating Income (Bopo)mentioning
confidence: 99%
“…Varghese and Thaha (2017) examined the efficiency of India's Kotak Mahindra Bank before and after its merger, providing results that show that the merger did help improve bank efficiency. Akpan, Aik, Wanke, and Chau (2018) collected information on listed companies on the Nigeria Stock Exchange from 1995 to 2012 and used Cost Efficiency Using Residual Income Valuation, Economic Value Added, and SFA to discuss postmerger operating performance of the listed companies. The results showed that, in the long run, in terms of operating performance, the acquired company improves more significantly than the main acquired company.…”
Section: Introductionmentioning
confidence: 99%
“…For efficiency analysis of bank mergers, most studies focused on postmerger efficiency evaluation, such as Sufian et al (2012), Zhu, Chen, and White (2014), Chaudhary and Arshad (2016), Devarajappa (2017), Veenstra et al (2017), Al‐Hroot (2015), Varghese and Thaha (2017), Akpan et al (2018), and Papadimitri et al (2019). However, postmerger efficiency evaluation cannot be used as an evaluation consideration for a financial holding company.…”
Section: Introductionmentioning
confidence: 99%